Pengaruh Solvabilitas dan Ukuran Perusahaan Terhadap Profitabilitas pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Mohammad Risky Arya Pratama; Dwi Rahayu; Sutikni Sutikni; Sri Harjanto (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
The purpose of this study is to determine the effect of solvency and company size on the profitability of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The population of this study was 11 pharmaceutical companies listed on the IDX for the period 2020-2023, the number of samples was 8 which were taken based on purposive sampling techniques. The type of data used includes secondary data that can be accessed through the company's website, www.idx.co.id. The analysis method used is multiple regression analysis processed with the SPSS program. The results of the study indicate that solvency has a negative and significant effect on profitability. Meanwhile, company size shows a negative insignificant effect on profitability.